2006
DOI: 10.1128/mcb.26.8.3243-3255.2006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Localization of Ras Requires Class C Vps Proteins and Functional Mitochondria in Saccharomyces cerevisiae

Abstract: Ras proteins are synthesized as cytosolic precursors, but then undergo posttranslational lipid addition, membrane association, and subcellular targeting to the plasma membrane. Although the enzymes responsible for farnesyl and palmitoyl lipid addition have been described, the mechanism by which these modifications contribute to the subcellular localization of Ras is not known. Following addition of the farnesyl group, Ras associates with the endoplasmic reticulum (ER), where palmitoylation occurs in Saccharomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 81 publications
1
32
1
Order By: Relevance
“…However, expression of the retrograde response gene CIT2 was induced in pep3 cells, even in nitrogen-rich medium, confirming earlier observations that vps class C mutants show mitochondrial defects (Fig. 1B) (16).…”
Section: Class C Vps Mutants Are Defective For Activating Ncr In Poorsupporting
confidence: 78%
“…However, expression of the retrograde response gene CIT2 was induced in pep3 cells, even in nitrogen-rich medium, confirming earlier observations that vps class C mutants show mitochondrial defects (Fig. 1B) (16).…”
Section: Class C Vps Mutants Are Defective For Activating Ncr In Poorsupporting
confidence: 78%
“…7). Evidence to support a role for vesicle trafficking in the regulation of Ras2p comes from a previous study that convincingly demonstrated that the disruption of the Class C VPS complex leads to mitochondrial localisation of Ras2p and respiratory defects (Wang and Deschenes, 2006). In addition we have recently demonstrated that mutations in the class C VPS machinery also result in the accumulation of ROS, formation of actin aggregates and failure to degrade Ras2p during the diauxic shift in a manner similar to that observed for Δwhi2 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast and adipocytes, palmitoylated Ras isoforms can also utilise a Golgi independent pathway to reach the plasma membrane [49,50]. Intriguingly, this pathway in yeast requires class C vps proteins that are classically associated with regulating endosome fusion [51]. The steady state distribution of the isoforms varies; whilst all Ras isoforms exhibit plasma membrane localisation, the extent of endomembranous labelling varies amongst isoforms and between cell types.…”
Section: Compartmentalisation Of Rasmentioning
confidence: 99%